Daily Functionality of People with Low Vision: The Impact of Visual Acuity, Depression, and Life Orientation—A Cross-Sectional Study - Mara Gkioka; Stavroula Almpanidou; Niki Lioti; Diamantis Almaliotis; Vasileios Karampatakis (Behavioural Neurology, 2024)
Background. Low vision (LV) has a significant negative impact on the activities of daily life as well as on the psychological health of patients. Objectives. The objective of this study is to investigate psychological, clinical, and demographic factors that may impact the daily functionality of patients with LV. Methods. A convenience sample of 53 patients, meeting the WHO criteria for LV, was recruited. Questionnaires on daily functionality, depression, and life orientation (in terms of optimism/pessimism) were administered along with a semistructured personal interview. Key Findings. The main results revealed a significant negative correlation between daily functionality and depression (r=−0.423, p<0.001). Conversely, there is a positive correlation between daily functionality and visual acuity (r=0.415, p<0.001), while years since diagnosis were negatively correlated with depression (r=−0.345, p<0.001). Depression seems to be a moderate predictor of a person’s daily functionality (β=−0.389, p<0.002), followed by visual acuity (β=−0.344, p=0.006), explaining the 31.1% of the total variance. Conclusions. The study supports a correlation between daily functionality and both depression and visual acuity. Optimism as a personality characteristic did not factor into the prediction model for daily functionality, but it showed a strong correlation with lower levels of depressive symptoms. This highlights the potential for developing coping strategies for chronic disease management. Recommendations. The study could serve as a useful guide and may urge clinicians to pay attention to the psychological evaluation of these patients, supporting their unique emotional needs. Mental health professionals can use patients’ positive resources to provide appropriate counseling and embrace the coping skills that encourage their engagement in activities of daily life.